2007
DOI: 10.1111/j.1467-8551.2007.00531.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Outcomes of Psychological Contract Breach in a Non‐Western Culture: The Moderating Role of Equity Sensitivity*

Abstract: This study tests the effects of psychological contract breach on several employee outcomes: workplace deviant behaviours directed at the organization (WD-O) and its organizational members (WD-I), in-role performance, and organizational citizenship behaviours directed at the organization (OCB-O) and its co-workers (OCB-I). It also examines the moderating effects of equity sensitivity in the relationship between breach and these outcomes. Data were collected from 162 sales executives and their direct supervisors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(122 citation statements)
references
References 49 publications
8
112
0
2
Order By: Relevance
“…In their seminal paper, Robinson and Rousseau (1994) showed that PCB is more the norm than the exception, and, when it happens, can lead to undermined trust between employee and employer, dissatisfaction among employees and even the dissolution of the relationship. Consistent with that, it has been shown that that PCB is negatively related to job satisfaction (Raja, Johns & Ntalianis, 2004), intention to stay in the organization (Turnley & Feldman, 2000), job performance (Johnson & O'Leary-Kelly, 2003), trust in the organization (Zhao et al, 2007), organizational citizen behaviors (Restubog, Bordia & Tang, 2007) and organizational commitment (Zhao et al, 2007). At the same time, PCB was shown to be positively correlated with counterproductive work behaviors (Bordia, Restubog & Tang, 2008), absenteeism and organizational cynicisms (Johnson & O'Leary-Kelly, 2003).…”
Section: Introductionsupporting
confidence: 64%
“…In their seminal paper, Robinson and Rousseau (1994) showed that PCB is more the norm than the exception, and, when it happens, can lead to undermined trust between employee and employer, dissatisfaction among employees and even the dissolution of the relationship. Consistent with that, it has been shown that that PCB is negatively related to job satisfaction (Raja, Johns & Ntalianis, 2004), intention to stay in the organization (Turnley & Feldman, 2000), job performance (Johnson & O'Leary-Kelly, 2003), trust in the organization (Zhao et al, 2007), organizational citizen behaviors (Restubog, Bordia & Tang, 2007) and organizational commitment (Zhao et al, 2007). At the same time, PCB was shown to be positively correlated with counterproductive work behaviors (Bordia, Restubog & Tang, 2008), absenteeism and organizational cynicisms (Johnson & O'Leary-Kelly, 2003).…”
Section: Introductionsupporting
confidence: 64%
“…Breach is the employees' cognitive evaluation of the difference between what is considered as obligation and what is done by employer in reality. Breach results in various undesirable individual and organizational outcomes which includes reduced job satisfaction (Orvis et al, 2008;Turnley & Feldman, 1999), reduced organizational commitment (Restubog, Bordia, & Tang, 2006), lowered performance (Robinson, 1996;Suazo & Stone-Romero, 2011), lowered organizational citizenship behavior (Restubog, Hornsey, Bordia, & Esposo, 2008;Robinson, 1996), increased burnout (Gakovic & Tetrick, 2003), increased deviant behaviors (Restubog, Bordia, & Tang, 2007), and heightened turnover intention (Turnley & Feldman, 2000;Raja et al, 2004).…”
Section: Concepts and Literature Review Psychological Contract Breachmentioning
confidence: 99%
“…In order to "get even" with the organization after a psychological contract breach, employees tend to reduce their commitment to the organization and display less organizational citizenship behaviors (Turnley et al, 2003). A recent study found that psychological contract breach was negatively related to supervisor rated OCB-I and OCB-O (Restubog et al, 2007). A meta-analysis of 51 empirical studies revealed that perceived psychological contract breach was negatively related to employees' citizenship behaviors (Zhao et al, 2007).…”
Section: Impact Of Psychological Contract Breach On Organizational CImentioning
confidence: 99%
“…For example, a psychological contract breach is negatively related to the employee's trust in management (Chelliah et al, 2009;Deery, Iverson, & Walsh, 2006;Zhao, Wayne, Glibkowski, & Bravo, 2007), job satisfaction (Gakovic & Tetrick, 2003;Zhao et al, 2007), intention to remain with the organization (Kickul et al, 2002;Zhao et al, 2007), employee performances (Restubog et.al, 2007;Suazo et al, 2005), citizenship behaviors Zhao et al, 2007), civic virtue behavior (Chambel & Alcover, 2011), and employee commitment (Johnson & O'Leary-Kelly, 2003;Raja et al, 2004) and positively related to workplace deviant behaviors (Bordia et al, 2008;Restubog et al, 2007), employees' neglect of job duties (Turnley & Feldman, 1998, 1999, job burnout (Chambel & Oliveira-Cruz, 2010), employees' cynicism about their employer (Johnson & O'Leary-Kelly, 2003), higher absenteeism (Deery et al, 2006;Johnson & O'Leary-Kelly, 2003), and revenge cognitions (Ahmed et al, 2007;Bordia et al, 2008). Such findings indicate that the psychological contract breach is negatively related with three forms of employee contributions to the organization: day-to-day performance, organizational citizenship behaviors, and intentions to remain with the organization (Robinson, 1996).…”
Section: Impact Of Psychological Contract Breachmentioning
confidence: 99%